(untitled) (Baghdad Science Journal, 2024)
Due to the importance of the extraction process in many engineering and medical industries, in addition to great interest in medicinal plants, in this research, microwave-assisted extraction has been applied to extract some active compounds from Rosmarinus officinalis leaves. The optimal extraction conditions were then determined by calculating the ratio and extraction efficiency. The process has also been described through kinetic study by applying five kinetic models, the Hyperbolic diffusion model, Power low model, the First order reaction model, Elovich’s model, and Fick’s second law diffusion model and determining their compatibility with the studies operation, and determining the kinetic constants for each model. The results of extracts showed that the best conditions are: the solvent is ethyl alcohol 80%, the capacity is 720W, and time is 6.5 min. For the kinetic study, all the studied models were appropriate to the applied extraction tip with high correlation coefficients, therefore, the kinetic constants of all these models were determined.